Content Of Innovation And Innovative Activity Of The Teacher - Barno Saydakhmedova, Munojat Makhkamova , Sayyora Rakhimova (International Journal of Advanced Science and Technology, 2020)
The article deals with analyzing the content of innovation and the essence of teacher’s innovative activity. The difference of innovation from any novelty is it needs to have a flexible mechanism for managing and controlling. In essence, innovation is a dynamic system for bringing innovation to a relationship or process. Introducing innovation as a system by itself represents the attitude or process of the relationship, firstly, the internal logic and, secondly, the gradual development and interaction of the innovation being introduced over a given period of time. Innovative activity is the main activity that determines the success of a teacher, and it is a qualitative reconstruction of the professional and methodical skills of the person. Innovative activity begins with the search for a new idea. Pedagogical innovation requires a new approach from the teacher as it focuses on addressing an important and complex issue in the educational process.